Baseline characteristics and outcome of stroke patients after endovascular therapy according to previous symptomatic vascular disease and sex - Peycheva, Marieta; Padlina, Giovanna; Genceviciute, Kotryna; Krasteva, Marina P.; Boronylo, Anna; Goeldlin, Martina B.; Müller, Madlaine; Wenz, Elena S.; Müller, Mandy D.; Hammer, Helly; Bücke, Philipp; Bigi, Sandra; et al. (Frontiers in Neurology, 2024)
The aim of this study was to investigate baseline characteristics and outcome of patients after endovascular therapy (EVT) for acute large vessel occlusion (LVO) in relation to their history of symptomatic vascular disease and sex.Methods: Consecutive EVT-eligible patients with LVO in the anterior circulation admitted to our stroke centre between 04/2015-04/2020 were included in this observational cohort study. All patients were treated according to a standardised acute ischaemic stroke (AIS) protocol. Baseline characteristics and successful reperfusion, recurrent/progressive in-hospital ischaemic stroke, symptomatic inhospital intracranial haemorrhage, death at discharge and at 3 months, and functional outcome at 3 months were analyzed according to previous symptomatic vascular disease and sex.Results: 995 patients with LVO in the anterior circulation (49.4% women, median age 76 years, median admission NIHSS score 14) were included. Patients with multiple vs. no previous vascular events showed higher mortality at discharge (20% vs.9.3%, age/sex-adjustedOR=1.43, p=0.030) and less independency at 3 months (28.8% vs. 48.8%, age/sex-adjustedOR=0.72, p=0.020). All patients and men alone with one or multiple vs. patients and men with no previous vascular events showed more recurrent/progressive in-hospital ischaemic strokes (19.9% vs. 6.4% in all patients, age/sex-adjustedOR=1.76, p=0.028) (16.7% vs. 5.8% in men, age-adjustedOR=2.20, p=0.035). Men vs. women showed more in-hospital symptomatic intracranial hemorrhage among patients with one or multiple vs. no previous vascular events (23.7% vs. 6.6% in men and 15.4% vs. 5.5% in women, OR=2.32, p=0.035/age-adjustedOR=2.36, p=0.035).Previous vascular events increased the risk of in-hospital complications and poorer outcome in the analyzed patients with EVT-eligible LVO-AIS. Our findings may support risk assessment in these stroke patients and could contribute to the design of future studies.